PELAKSANAAN RESTITUSI BAGI KORBAN TINDAK PIDANA PENIPUAN INVESTASI DENGAN SKEMA ROBOT TRADING: STUDI KASUS DI LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN (LPSK) - Rajib Aliwafa Zarkasy; Maria Novita Apriyani (Universitas Labuhanbatu, 2026)
Fraudulent investment schemes using the Viral Blast Global robot-trading platform caused substantial financial losses and raised legal problems in fulfilling victims’ rights to restitution. This study aims to analyze the implementation of restitution for victims of fraudulent investment crimes using a robot-trading scheme, as well as the obstacles faced by the Witness and Victim Protection Agency (LPSK) in fulfilling victims’ rights. This research employs an empirical juridical method with case, structural, and statutory approaches based on the KUHAP, Law Number 31 of 2014, Government Regulation Number 35 of 2020, Government Regulation Number 7 of 2018, and Supreme Court Regulation Number 1 of 2022. The data were obtained from interviews at LPSK and secondary legal materials, including official documents and the Surabaya District Court Decision Number 1466/Pid.Sus/2022/PN Sby. The findings show that LPSK has carried out administrative verification, substantive examination, the establishment of the Compensation Assessment Team, and the submission of restitution before the court decision. However, the implementation of restitution faces obstacles in the form of overlapping execution authority, difficulties in proving victims’ financial losses, and low victim participation. The analysis also shows that the court ruling assigning execution duties to LPSK creates disharmony with the existing legal framework, since execution should legally fall under the authority of the prosecutor. This study concludes that restitution implementation in the Viral Blast Global case has been carried out, but it still requires regulatory harmonization, clearer execution mechanisms, and a more adaptive evidentiary framework for digital-based crimes.Keywords: Restitution; Victims’ Rights; Fraud Offenses; Robot Trading; LPSK.